Analysis of Politeness Strategy of Directive Addressed to Jojo in “Jojo Rabit” Film - Denia Amanda Putri (PRASASTI: Journal of Linguistics, 2023)
The utterance means not only word as a statement but also to perform action or namely speech act. In this paper, directive speech act was analyzed to classify the politeness strategy of directive extended to Jojo as the main character in Jojo Rabbit film. This research is conducted by using descriptive qualitative method. The data were examined using domain, taxonomy, componential, and cultural theme analysis. The findings show that seven types of directives are found from 122 data gathered. Those are question, request, advice, command, dare, ban, and begging. Question is the most directive found as the speaker often asks about Jojo’s condition and opinion about something. The directives are spread throughout the narrative structures of the film with various contexts of situations between participants as the source of data. Politeness strategies found in the film are bald on record, positive politeness strategy, and negative politeness strategy. The strategy mostly used is bald on record (59 data). It is followed by positive politeness strategy (51 data) and negative politeness strategy (12 data). Bald on record is used the most when the speakers address questions to Jojo. The directive "question" also becomes the most frequently found when the speakers use positive politeness strategy and negative politeness strategy.